Inklusi Keuangan Melalui Literasi Keuangan, Modal Sosial, dan Teknologi Finansial: Desa Blang Kecamatan Syamtalira Aron Kabupaten Aceh Utara - Bustami, Koko; Saifrizal, Muhammad; Inuzula, Lakharis (Green Publisher Indonesia, 2025)
In this era of digitalization, the development of technology is so rapid, we can feel this from the ease of all jobs that used to be very complex, such as the existence of financial inclusion systems and financial technology, namely banks or e-banking. Banks play an important role for society, this has proven to be a brilliant solution in financial transactions and transfers. So in this case, the role of financial literacy, financial technology and social capital is very important to increase financial inclusion. This study aims to see how the influence of financial literacy on financial inclusion, the influence of social capital on financial inclusion, and financial technology on the financial inclusion of the people of Blang Village